Preparation and Characterization of Montelukast Sodium ( SMLT ) as a Dual Sustained Release Buccal Strips - I.Khalil, Yehia (Iraqi Journal of Pharmaceutical Sciences, 2017)
An oral bi layer sustained release (SR) strips of Sodium Montelukast SMLT , which is selective leukotriene antagonist , used for patients suffered from mid-night asthma , were prepared successfully ,using different polymers, like guar gum , carrageenan , and xanthan gum , by solvent casting method . The results obtained by this study revealed ,that best fast dissolving film of SMLT was loaded in carrageenan polymer 57% w(30mg.) , with acceptable physical properties, like film thickness , elastic endurance and surface pH . Besides to that , the disintegration time , and cumulative 80% drug release were estimated 22 seconds and 3.7 minutes , respectively .On the other hand , the sustained release film ( FSR6-7 ) as a second layer , appear to be the most promised layer of SMLT loaded in 50 % w (15mg.) PVP K17 , with respect to its film thickness, elastic endurance and , surface pH . Moreover the , the disintegration time of the second layer film was 21seconds , and the time for 50% drug release was 15 minutes extended for 4hours of 100% drug release . Meanwhile , the investigation of possible interference between the drug , and, polymers used revealed no evidence of this effect ,using FTIR , and SEM technique . In an attempt to evaluate the extended release effect of the selected formula , SingulairÂ® plain tablet as a marketed product was used , the result gave more than 4 hours of selected formula , compared with 30 minutes to marketed product SingulairÂ® . The overall results candidates the selected FSR6-7 formula as a promised bi layer buccal fast , as compliance and extended therapy for asthmatic mid- night patients. Keywords: Montelukast sodium, Dual buccal strips, Guar gum, Xanthan gum, Carrageenan.